Quantitative trait loci for sorghum grain morphology and quality traits: Toward breeding for a traditional food preparation of West-Africa. (January 2019) - Guindo, Diarah; Teme, Niaba; Vaksmann, Michel; Doumbia, Mohamed; Vilmus, Ingrid; Guitton, Baptiste; Sissoko, Aliou; Mestres, Christian; Davrieux, Fabrice; Fliedel, Geneviève; Kouressy, Mamoutou; Courtois, Brigitte; et al.
Abstract: One of the most frequently consumed sorghum food in Mali is a thick porridge, known as tô. Many grain traits contribute to its firmness and color, which are the most important qualities for consumers. These traits are related to chemical composition, physical properties, but also grain size, shape, glume adherence and color, pericarp thickness, or the presence of a testa. Quantitative trait loci for tô consistency, tô color, 16 grain traits, as well as day to flowering and grain yield, were investigated in two elite breeding populations, involved in a marker assisted selection program. A total of 51 and 71 QTLs were detected for P114 and P118, respectively. Several QTLs with high R 2 corresponded to major genes segregating in the populations such as the Z gene for pericarp thickness, the B2 and B1 genes for testa presence, the P gene for anthocyanin, and a QTL for flowering time. Many QTLs with moderate effect were detected for grain attributes associated to tô quality, without showing antagonism between grain quality and yield. The results of this study will contribute to producing new varieties combining grain productivity and grain quality favorable alleles, through the use of marker assisted selection. Highlights: A QTL detection conducted in breeders' populations as part of a marker-assisted selection program. Major genes with large effect still segregates in breeding population derived from elite material. There is no major antagonism to jointly improve grain yield and grain quality in West-African sorghum germplasm.